Genomic loci associated with leaf abscission contribute to machine picking and environmental adaptability in upland cotton (Gossypium hirsutum L.) - Hongge Li; Xiangru Wang; Ning Qin; Daowu Hu; Yinhua Jia; Gaofei Sun; Liangrong He; Hengheng Zhang; Panhong Dai; Zhen Peng; Nianchang Pang; Zhaoe Pan; et al. (Journal of Advanced Research, 2024)
Introduction: Defoliation by applying defoliants before machine picking is an important agricultural practice that enhances harvesting efficiency and leads to increased raw cotton purity. However, the fundamental characteristics of leaf abscission and the underlying genetic basis in cotton are not clearly understood. Objectives: In this study, we aimed to (1) reveal the phenotypic variations in cotton leaf abscission, (2) discover the whole-genome differentiation sweeps and genetic loci related to defoliation, (3) identify and verify the functions of key candidate genes associated with defoliation, and (4) explore the relationship between haplotype frequency of loci and environmental adaptability. Methods: Four defoliation-related traits of 383 re-sequenced Gossypium hirsutum accessions were investigated in four environments. The genome-wide association study (GWAS), linkage disequilibrium (LD) interval genotyping and functional identification were conducted. Finally, the haplotype variation related to environmental adaptability and defoliation traits was revealed. Results: Our findings revealed the fundamental phenotypic variations of defoliation traits in cotton. We showed that defoliant significantly increased the defoliation rate without incurring yield and fiber quality penalties. The strong correlations between defoliation traits and growth period traits were observed. A genome-wide association study of defoliation traits identified 174 significant SNPs. Two loci (RDR7 on A02 and RDR13 on A13) that significantly associated with the relative defoliation rate were described, and key candidate genes GhLRR and GhCYCD3;1, encoding a leucine-rich repeat (LRR) family protein and D3-type cell cyclin 1 protein respectively, were functional verified by expression pattern analysis and gene silencing. We found that combining of two favorable haplotypes (HapRDR7 and HapRDR13) improved sensitivity to defoliant. The favorable haplotype frequency generally increased in high latitudes in China, enabling adaptation to the local environment. Conclusion: Our findings lay an important foundation for the potentially broad application of leveraging key genetic loci in breeding machine-pickable cotton.